Model Implementasi Kebijakan Pengembangan Ilmu Berparadigma Islam dalam Ekselerasi Pencapaian Visi dan Misi Konversi IAIN SUSQA Pekanbaru ke UIN SUSKA Riau (Penelitian Kebijakan dan Pengembangan) - Amri Darwis (Lembaga penelitian dan pengabdian kepada Masyarakat, 2013)
This article is the result of research evaluation Science Development policies Islamic paradigm. Islamic science development policy paradigm is the main mission of the college conversion to Islam original status of the State Islamic Institute into the State Islamic University (UIN) of Suska Riau. Because the image is viewed of the State Islamic Institute still stuck on the dichotomy of science, even focusing on the religious sciences only by ignoring the science world. Then proposed a new mission “ Integrating Science with Islam “. This of the development policy paradigm of Islamic science as the main mission of conversion of the State Islamic Institute to State Islamic University of Suska Riau is still lagging behind other elements of progress very policy implementation, in accordance with the method of policy implementation model development research conducted the trials in the Faculty of Education and Teaching, and Faculty of Economics and Social Sciences. The result, some of the models that were developed as a model top down, Buttom Up, and Hybridge, Hybridge conducted in the presence of the faculty is not yet a model, a guide, or guide the development of science in the Islamic paradigm faculty in general and religious faculty.